HUBUNGAN JENIS KELAMIN TERHADAP GAYA MANAJEMEN KONFLIK DI KABUPATEN TABALONG - Suryani, Lilis; Fahruji Rahman (stiatabalong.ac.id, 2024)
Tabalong regency has the highest number of dispute and conflict cases handle in South Kalimantan from 2017 to 2021. Service officers, men and women within the Tabalong Regency Government definitely have a certain style when dealing with conflict situations. The aim of this research is to determine the dominant conflict management style based on gender, as well as analyze and test the relationship between gender and conflict management style. This research uses a quantitative approach with a survey method involving 5 (five) agencies in Tabalong Regency. The research sampling technique is convenience sampling. 291 questionnaires were distributed, 270 questionnaires were returned, while 206 questionnaires were completely filled out. Data analysis used descriptive statistics, namely frequency tabulation and cross tabulation, followed by testing the significance of the relationship between sex and conflict management style using Chi-Square with the help of software SPSS. Men and women have different conflict management styles, but in general managers can use a compromise style for situations that require quick, short-term solutions. The dominant responses of male employees when facing conflict situations are competition style, compromise style, and accommodation style. Meanwhile, the dominant responses of female employees are collaboration style and avoidance style. Chi-Square test results show that the relationship between gender and conflict style is generally not significant, except for avoidance style. Keywords: Gender, Conflict Style, Conflict Management